2011
DOI: 10.7439/ijbr.v2i2.85
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Screening of the Bark of Adenanthera Pavonina (L.)

Abstract: Adenanthera pavonina L. syn. Red Sandalwood, (Fabaceae) is an unarmed deciduous tree and its bark is traditionally used for treatment of various disease conditions in gonorrhea, haematuria, ulcers, it is astringent, vulnerary and aphrodisiac in nature. The aim of the present study was to evaluate the qualitative analysis of phytochemicals and antibacterial activity of solvent extracts of Adenanthera pavonina bark. Antimicrobial activity of different solvent extracts of Adenanthera pavonina bark were tested aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 4 publications
0
14
0
1
Order By: Relevance
“…Among the plants tested, the aqueous extract of A. odoratissima showed highest TPC (532.5 mg GAE/100 μL) followed by A perusal of the literature revealed that, among the 42 plants screened only few plants were reported for their antimicrobial and antioxidant potencies. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Further, no reports are available pertaining to the antibacterial and antioxidant activities of solvent extracts of these plants. To the best of our knowledge, this is the first report describing the antibacterial and antioxidant activities of the tested plants.…”
Section: Resultsmentioning
confidence: 99%
“…Among the plants tested, the aqueous extract of A. odoratissima showed highest TPC (532.5 mg GAE/100 μL) followed by A perusal of the literature revealed that, among the 42 plants screened only few plants were reported for their antimicrobial and antioxidant potencies. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Further, no reports are available pertaining to the antibacterial and antioxidant activities of solvent extracts of these plants. To the best of our knowledge, this is the first report describing the antibacterial and antioxidant activities of the tested plants.…”
Section: Resultsmentioning
confidence: 99%
“…Another study using extracts from A. pavonina bark at the concentration of 25, 50 and 75 mg/well, there was effective inhibition of the diameter of zones against both Gram-positive (B. subtilis and S. epidermidis) as well as Gram-negative bacteria (Enterobacter aerogenes, P. aeruginosa, Salmonella typhimurium) by disc diffusion method. However, the ethanolic and aqueous extracts evidenced the highest activity against all the tested bacteria (Hussain et al, 2011).…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 93%
“…One very promising approach is the screening of antiviral products derived from natural sources, especially plants. Adenanthera pavonina L., Caesalpinia ferrea Mart., and Dimorphandra gardneriana Tull are native plants from Caatinga biome of Northeastern Brazil and have been used for the treatment of many diseases: A. pavonina has been reported to possess antibacterial [ 15 , 16 ], antioxidant [ 17 ], anthelmintic [ 18 ], antihyperlipidemic [ 19 ], blood pressure lowering [ 20 ], and anti-inflammatory [ 21 ] effects. Pharmacological properties of C. ferrea include hypoglycemic [ 22 , 23 ], antimicrobial [ 24 ], anticancer [ 25 , 26 ], anti-inflammatory [ 27 , 28 ], and analgesic [ 28 ].…”
Section: Introductionmentioning
confidence: 99%